Teenagers Entertainment Satisfaction in Watching Talk Show Program through Youtube - Haqqu, Rizca; Hastjarjo, Sri; Slamet, Yulius (Universitas Semarang, 2019)
This study was conducted based on the results of research from several survey institutions which explained that there was an indication of shifting patterns from old media to the new media. The researchers wanted to know the level of satisfaction of the youth in using the new media among the community with the students of Universitas Sebelas Maret, generation 2015 to 2017. In this study, the researchers used the Uses and Gratification approaches. The researchers also use quantitative analysis and the Slovin formula to calculate samples of respondents from each generation. The frequency distribution analysis technique was used to calculate the frequency of data and then procentaged. The result of this study is that there is a high level of satisfaction where the majority of the respondents feel that they get the satisfaction they want or look for when watching talk show program through Youtube.